ONE OF THE POSSIBLE MECHANISMS OF THE REPLENISHMENT OF HYDROCARBON RESERVES - Dmitrievskii A.N.; Balanyuk I.E.; Karakin A.V. (My University, 2007)
An unusual phenomenon, the appearance of oil inflow in old oilfields and wells worked out long ago, has long been known to many researchers. At present, it is more expedient to obtain the increment of mineral reserves through revision of geological–geophysical materials on old oilfields than to carry out expensive geological exploration. This work presents one of the possible concepts pertaining to the phenomenon mentioned above.